Pelatihan Pembuatan Media Pembelajaran Bahasa Arab Berbasis Lectora di MA Darullughah Wadda'wah Bangil Pasuruan - Musytahar Ali Wardana (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Technological advancements in the era of the Industrial Revolution 4.0 have demanded transformations across various sectors, including education. This Community Service Program (PKM) aims to enhance the competence of Islamic Religious Education (PAI) teachers at MA Darullughah Wadda’wah Bangil through training on the development of instructional media using Lectora Inspire. This application offers interactive features that enable teachers to create multimedia-based teaching materials and automated, varied assessments. The method used includes training, mentoring, and discussion through a participatory approach. The results of the training indicate high enthusiasm among teachers, who were able to develop contextual and engaging learning media tailored to the characteristics of their students. This program not only improves the quality of PAI instruction but also promotes the transformation of teachers into creative and adaptive facilitators in response to technological advancements. The training serves as a strategic model for fostering modern, interactive, and relevant Islamic education in today’s digital era